Factors affecting sales performance of farm machinery at selected dealers in Selangor / Hilman Nazmi Abdul Razak - Abdul Razak, Hilman Nazmi (Faculty of Plantation And Agrotechnology, 2017)
People now days make decision in purchasing in any aspect of their life. The sellers have the problem to acknowledge the behavior of the customer. All the decisions regarding marketing strategies must be refer to the customer behavior. The objective for this study is to identify the factor affecting the selling performance of farm machinery and to evaluate by ranking the identified factors in accordance with their effect on farm machinery selling performance in Selangor state. The study is carried out in Selangor state. Both primary and secondary data are used for this research. The study has collected primary data from the dealer of farm machinery in Selangor. Factor analysis was used to find out the most influencing factor that is considered by the respondent which is the dealer in the selling performance factor of farm machinery. It is found that as ranking that based on the respondents, product is ranked first and followed by reputation, spare and parts, marketing strategies and economic that is considered for selling farm machinery by following the customer behavior.